2016
DOI: 10.5935/abc.20160149
|View full text |Cite
|
Sign up to set email alerts
|

In-Lab Upfront Use of Tirofiban May Reduce the Occurrence of No-Reflow During Primary Percutaneous Coronary Intervention. A Pilot Randomized Study

Abstract: BackgroundDespite successful opening of culprit coronary artery, myocardial reperfusion does not always follows primary percutaneous coronary intervention (PPCI). Glycoprotein IIb/IIIa inhibitors are used in the treatment of no-reflow (NR), but their role to prevent it is unproven.ObjectiveTo evaluate the effect of in-lab administration of tirofiban on the incidence of NR in ST-elevation myocardial infarction (STEMI) treated with PPCI.MethodsSTEMI patients treated with PPCI were randomized (24 tirofiban and 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…STEMI patients with a high thrombus load, intracoronary tirofiban treatment helped enhance coronary blood flow and myocardial perfusion while also lowering the risk of 30day MACE. Furthermore, tirofiban increases vascular endothelial function [16]. International studies have shown that early administration of a platelet GP IIb/IIIa receptor antagonist improves the effectiveness of PCI and the prognosis of reperfusion treatment in patients with acute coronary syndrome [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…STEMI patients with a high thrombus load, intracoronary tirofiban treatment helped enhance coronary blood flow and myocardial perfusion while also lowering the risk of 30day MACE. Furthermore, tirofiban increases vascular endothelial function [16]. International studies have shown that early administration of a platelet GP IIb/IIIa receptor antagonist improves the effectiveness of PCI and the prognosis of reperfusion treatment in patients with acute coronary syndrome [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The improved treatment received by STEMI patients is PPCI in comparison to medical treatment 4 . Over the past 10 years, the best treatment for acute myocardial infarction (MI) is PPCI to achieve complete reperfusion and thus decrease the death rate 16 . The advantages of PCI are improvement in myocardial blood flow and normal TIMI flow grade, thus fewer chances of cardiovascular events 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in patients with hyperthrombotic lesions that achieve complete recanalization of infarcted coronary arteries, pre-coronary administration of drugs, such as glycoprotein IIb/IIIa receptor antagonists or sodium nitroprusside, should be fully evaluated based on the nature of the thrombus extracted from the coronary arteries. Calcium antagonists[33,34] are important to reduce the occurrence of slow blood flow or no reflow.…”
Section: Discussionmentioning
confidence: 99%